Competence and Compensation Influence on Work Performance and Employee Career Development Study on Bank Indonesia Representative Office in East Java - Apriyanto, Guntur; Sunaryo, Hadi; Salim, Muhammad Agus (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyse the effect of competence and compensation on job performance and employee career development, both directly and indirectly through the mediating variable of job performance. The research was conducted on employees of the Representative Office of Bank Indonesia in East Java with a quantitative approach and analysis techniques using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). Data were obtained through distributing questionnaires to 60 respondents representing various Representative Offices of Bank Indonesia in the region. The results of the analysis show that competence and compensation have a significant effect on employee performance. Furthermore, job performance also has a positive effect on career development. In addition, it was found that competence and compensation also indirectly affect career development through the mediation of work performance.These findings imply that increasing competence and providing appropriate compensation can be an important strategy in supporting employee career development through improved work performance. Therefore, organisational management is expected to pay more attention to aspects of competence, compensation, and performance evaluation as a whole